2021
DOI: 10.3389/fmolb.2020.605862
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of COVID-19 Patients Based on the Results of Nucleic Acid and Specific Antibodies and the Clinical Relevance of Antibody Levels

Abstract: Combination of nucleic acid and specific antibody testing is often required in the diagnosis of COVID-19, but whether patients with different nucleic acid and antibody results have different laboratory parameters, severities and clinical outcomes, has not yet been comprehensively investigated. Thus, according to different groups of nucleic acid and antibody results, we aimed to investigate the differences in demographic characteristics, and laboratory parameters among the different groups and predict their cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…These findings are due to variation in serology to symptom onset interval. (18) The study also did not find a statistically significant correlation between antibody tires with AKI, mechanical ventilation, ICU requirement, septic shock and mortality.…”
Section: Discussionmentioning
confidence: 72%
“…These findings are due to variation in serology to symptom onset interval. (18) The study also did not find a statistically significant correlation between antibody tires with AKI, mechanical ventilation, ICU requirement, septic shock and mortality.…”
Section: Discussionmentioning
confidence: 72%
“…1 study was found by manually searching ( Zeng et al, 2020 ).Of these, 1 meeting abstract, 2 not written in the English language, 40 not relevant, 2 reviews were excluded. The full text of 33 remained studies was assessed for eligibility and 12 case reports or case series ( Horii et al, 2020 ; Inoue et al, 2020 ; Ito et al, 2020 ; Nakamura et al, 2020 ; Scarpati, 2020 , Shibata et al, 2020 ; Shimazu et al, 2020 ; Zeng et al, 2020a ; Fukada et al, 2021 ; Sumimoto et al, 2021 ; Suzuki et al, 2021 ; Yamaya et al, 2021 ), 2 studies that did not report the results clearly ( Miyagami et al, 2021 ; Takeshita et al, 2021 ), 3 studies that did not classify patients based on disease severity ( Frix et al, 2020 ; Chen et al, 2021a ; Scotto et al, 2021 ) and 1 preprint study ( Alimova et al, 2020 ) were excluded. Finally, 15 studies identified as relevant and entered the quality assessment ( Awano et al, 2020 , d'Alessandro et al, 2020a , d'Alessandro and Cameli, 2020 , d'Alessandro et al, 2020b ; Frix et al, 2020 ; jp, 2020 , Saito et al, 2020 ; Wang et al, 2020 ; Xue et al, 2020 ; Anai et al, 2021 ; Bergantini et al, 2021 ; Chen et al, 2021 , d’Alessandro et al, 2021 ; Deng et al, 2021 ; He et al, 2021 ; Peng et al, 2021 ; Scotto et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Our results also support the necessity of boosters, which is why the Chinese government is actively promoting boosters. On the other hand, high IgG levels can effectively reduce the probability of symptomatic infection in children and promote a virus-negative conversion ( 14 , 24 ). Fever, gastrointestinal symptoms, AST, and LDH are related to the severity of the disease ( 25 , 26 ).…”
Section: Discussionmentioning
confidence: 99%